Forensic gait analysis : principles and practice - Birch, Ivan; Nirenberg, Michael; Vernon, Wesley; Birch, Maria (Boca Raton : CRC Press, 2020)
Gait analysis is the systematic study of human walking, using the eye and brain of experienced observers, augmented by instrumentation for measuring body movements, body mechanics, and the activity of the muscles. Since Aristotle's work on gait analysis more than 2000 years ago, it has become an established clinical science used extensively in the healthcare and rehabilitation fields for diagnosis and treatment. Forensic Gait Analysis details the more recent, and rapidly developing, use of gait analysis in the forensic sciences. The book considers the use of observational gait analysis, based on video recordings, to assist in the process of identification or exclusion. With the increase in use of CCTV and surveillance systems over the last 20 to 30 years, there has been a steady and rapid increase in the use of gait as evidence. Currently, gait analysis is widely used in the UK in criminal investigations, with increasing awareness of its potential use in the US, Europe, and globally. The book details the history of the science, current practices, and of the emergent application to establish best-practice standards that conform to those of other forensic science disciplines. Engagement with the Forensic Science Regulator, and the Chartered Society of Forensic Sciences in the UK, and the International Association for Identification has helped to ensure and enhance the quality assurance of forensic gait analysis. However, there remains a fundamental lack of standardized training and methodology for use in evidentiary and investigative casework. This book fills that void, serving as one of the first to describe the current state of practice, capabilities and limitations, and to outline methods, standards of practice and expectations of the gait analyst as a forensic practitioner. Forensic Gait Analysis reflects current research and forensic practice and will serve as a state-of-the-art guide to the use of gait analysis in the forensic context--for both education and training purposes. It will be a welcome addition to the libraries of professionals in the areas of podiatry, gait analysis, forensic video analysis, law enforcement, and legal practice.
Foreword: Anya Hunt, Chief Executive Officer of the Chartered Society of Forensic Sciences Preface: Ivan Birch Contributors Chapter 1: Introduction Ivan Birch and Wesley Vernon Chapter 2: The history of the use of gait analysis as evidence Michael Nirenberg Chapter 3: Fundamentals of human gait and gait analysis Ambreen Chohan, Jim Richards and David Levine Chapter 4: The legal context of forensic gait analysis Part 1: The legal context in North America Emma Cunliffe Part 2: The legal context in the United Kingdom Graham Jackson Chapter 5: The development of the forensic gait analysis quality assurance process in the UK Sarah Reel Chapter 6: Initial contact, preliminary assessment of footage and defining the task Ivan Birch Chapter 7: Analysing the questioned and reference footage Ivan Birch Chapter 8: Comparison of gait and evaluation Ivan Birch Chapter 9: Writing expert witness reports Part 1: General principles, requirements and pitfalls Roger Robson and Claire Gwinnett Part 2: Writing forensic gait analysis reports Ivan Birch Chapter 10: Presenting gait evidence in court Ivan Birch Chapter 11: Psychology of perceptual error in forensic practice Liam Satchell Chapter 12: Probative value of gait analysis Graham Jackson and Ivan Birch Chapter 13: Case study 1 -- Berry's One Stop Store robbery Michael Nirenberg Case study 2 -- arson of a business premises Maria Birch Case study 3 -- two armed bank robberies Ivan Birch Appendix 1 Sheffield features of gait tool Index
OCLC-licensed vendor bibliographic record.
Keywords: Forensic sciences; Forensic podiatry; Gait in humans; LAW / Criminal Law / General; TECHNOLOGY / Industrial Health & Safety